Pengaruh Financing To Deposit Ratio (FDR) Dan Biaya Operasional Pendapatan Operasional (BOPO) Terhadap Profitabilitas Dengan Non Performing Financing (NPF) Sebagai Variabel Intervening Pada Bank Muamalat Indonesia Periode 2014-2022 - Yulia Putri; Lemiyana; Fakhrina (CV. ITTC INDONESIA, 2024)
This research was conducted to determine the magnitude of the influence of FDR and BOPO on ROA with NPF intervention at Bank Muamalat Indonesia for the 2014-2022 period. The data used comes from secondary sources, namely financial reports taken from the official BMI website. This research method is a descriptive quantitative approach using SPSS 25 as a data processing program. The results of this research indicate that FDR and BOPO have a significant effect on ROA, FDR and BOPO together have an effect on ROA. Furthermore, NPF cannot significantly mediate FDR or BOPO on ROA.